PENGALAMAN SPRITUAL PASIEN KANKER KOLON DENGAN KOLOSTOMI PERMANEN: STUDI FENOMENOLOGI - Arafah, Masniati; Saleh, Ariyanti; Kaelan, Cahyono; Yusuf, Saldy (Journal of Islamic Nursing, 2017)
Background: The spiritual aspect is the most challenging thing in a permanent colostomy Muslim patient. The spirituality of a Muslim's religious perspective is influenced by religious practice or ritual. Installation of permanent colostomy leads to uncontrolled expulsion of feces (feces) and uncontrolled gas. This condition will give effect of ritual change of keagaaman to a Muslim that will influence spiritual. Method: This research used qualitative method of phenomenology approach, the selection of participants by purposive sampling chosen in accordance with inclusion criteria. Data collection is done through in-depth interviews, by providing open questions, voice recorder and field notes. Results of the research were: (1) positive spiritual change, (2) acceptance response to colostomy action, (3) change in the implementation of worship, (4) need guidance in conducting worship, (5) hope to further improve the quality of his worship. Conclusion: There was a positive spiritual change in the condition of permanent colostomy. However it affects the implementation of ritual worship in patients of Muslim patients.